HUMANITARIAN RELATIONS OF UZBEKISTAN AND AZERBAIJAN IN THE YEARS OF THE SECOND WORLD WAR (Scientific journal of the Fergana State University, 2023)
Based on the analysis of a wide range of sources and archival data, the history of humanitarian relations between Uzbekistan and Azerbaijan and their friendly ties to date are considered. The article also uses the data of the periodical press of the period of the Second World War.